2007
DOI: 10.1037/0022-006x.75.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Judging mental disorder in youths: Effects of client, clinician, and contextual differences.

Abstract: Using a vignette-based, mailed survey of 1,401 experienced psychologists, psychiatrists, and social workers, the authors examined how clients' race/ethnicity and clinicians' professional and social characteristics affect their judgment of mental disorder among antisocially behaving youths. Vignettes described problematic behaviors meeting the Diagnostic and Statistical Manual of Mental Disorders (4th ed.; DSM-IV; American Psychiatric Association, 1994) criteria for conduct disorder but contained contextual inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…Existing research offers evidence that experienced clinicians are sensitive to the social context surrounding adolescent antisocial behavior, and that they judge youth as less likely to have a mental disorder when context suggests the behavior might be a normal reaction to a harsh environment, rather than irrational responses resulting from internal dysfunction (Hsieh 2001;Hsieh andKirk 2003, 2005;Pottick et al 2003Pottick et al , 2007Wakefield et al 2002Wakefield et al , 2006. Other research studies have found that clinicians differentially use contextual information to weigh the importance of symptoms in judging whether a youth should be considered as having a diagnosis of conduct disorder (De Los Reyes and Marsh 2011;Marsh et al 2016), and have demonstrated that contextual information not only influences how clinicians arrive at diagnoses, but can also influence their judgments about other aspects of the clinical encounter, such as prognosis, need for professional help, and appropriateness of medication .…”
mentioning
confidence: 99%
“…Existing research offers evidence that experienced clinicians are sensitive to the social context surrounding adolescent antisocial behavior, and that they judge youth as less likely to have a mental disorder when context suggests the behavior might be a normal reaction to a harsh environment, rather than irrational responses resulting from internal dysfunction (Hsieh 2001;Hsieh andKirk 2003, 2005;Pottick et al 2003Pottick et al , 2007Wakefield et al 2002Wakefield et al , 2006. Other research studies have found that clinicians differentially use contextual information to weigh the importance of symptoms in judging whether a youth should be considered as having a diagnosis of conduct disorder (De Los Reyes and Marsh 2011;Marsh et al 2016), and have demonstrated that contextual information not only influences how clinicians arrive at diagnoses, but can also influence their judgments about other aspects of the clinical encounter, such as prognosis, need for professional help, and appropriateness of medication .…”
mentioning
confidence: 99%
“…Several vignette studies have begun such investigations. For example, Pottick et al (2007) found differences among psychologists, psychiatrists, and social workers in their judgment of the existence of mental disorder in a vignette youth with symptoms of conduct disorder. In another report from the same data set, Kirk and Hsieh (2004) showed that social workers, in relation to psychologists and psychiatrists, were less likely to make a diagnosis of conduct disorder, were more likely to use other DSM-IV diagnoses (especially adjustment disorders), and were more likely to report no diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…One measurement strategy that may help to close some of the gaps of traditional survey methods described in our review is the use of analogue, vignette-based techniques which present realistic case situations on which respondents report their beliefs, feelings, attitudes, or judgments. The use of vignettes in the field of mental health has grown in recent years to include both national samples (e.g., Kirk et al 1999;Pescosolido et al 2008;Pottick et al 2003Pottick et al , 2007Wakefield et al 1999) and regional and local ones (Chavez et al 2010;Mukolo and Heflinger 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations